PENGARUH STRES KERJA DAN KEPRIBADIAN TERHADAP KINERJA GURU DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL MODERATING (Studi Kasus Di SMP PL Cabang Semarang, Salatiga, dan Ambarawa) - Yoh. Ari Wibowo, 12.52.02.0217; Bassiya, R. (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of the research/study is to examine the influence of working stress and personality.toward the teachers performance in Junior High School Pangudi Luhur Semarang, Salatiga,Ambarawa branches is moderated by organization of culture.The research/study used 118 teachers of Junior High SchoolÂ Pangudi Luhur Semarang, Salatiga, Ambarawa branches populations. The research methodÂ used regression by interaction moderation. Based on the result of the research/study can be concluded as follow:working stress didntÂ give positive influence and significant toward the teachers performance. Personality has positive influence and significant toward teachers performance. Organization of culture influence positive and significant toward teachers performance. The influence of stress toward teachers performance is moderated by organization of culture, and the influence of personality toward teachers performance is moderated by organization of culture. Keywords: Work Stress, Organizational Culture, Personality and Teacherâs Performance